Chitosan edible films of shrimp waste as food packaging, friendly packaging. - Nurhayati Nurhayati; Agusman Agusman (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2011)
In an effort to reduce environmental pollution, edible film chitosan has been developed recentlyto maximize the utilization of shrimp waste and to promote the use of environmentally friendlypackaging. Chitosan is obtained through the process of deproteination, demineralization,depigmentation, and deacetylation of chitin. The next phase is dissolving chitosan in acid solventwith addition of plasticizer, followed by printing and drying. Edible chitosan film is applied as acoating on fresh fruits, meat products, sausages and other food products. The advantages ofedible chitosan film is its biodegradability, edibility, and anti microbial activity.